Rat lungworm survives winter: experimental overwintering of Angiostrongylus cantonensis larvae in European slugs - Anettová, Lucia; Šipková, Anna; Izquierdo-Rodriguez, Elena; Velič, Vivienne; Modrý, David (Parasitology, 2023)
The rat lungworm Angiostrongylus cantonensis is a metastrongyloid nematode that causes neurological disorders in its accidental hosts, including humans. This invasive pathogen is native to Southeast Asia and adjacent regions and is gradually expanding its distribution to tropical and subtropical areas with new foci discovered near temperate regions. The parasite has a complex life cycle with a range of gastropods serving as intermediate hosts. A broad spectrum of poikilotherm vertebrates and invertebrates can serve as paratenic hosts. Since it has already been demonstrated that other, non-zoonotic metastrongyloids can survive in their intermediate hosts during the winter, the aim of our study was to evaluate the survival of A. cantonensis third-stage larvae in experimentally infected slugs (Limax maximus) kept at 4.5–7°C for 60 days. Third-stage larvae of A. cantonensis survived the period of low temperature and remained capable of infecting definitive hosts (laboratory rats) afterwards, even though their numbers dropped significantly. These results suggest that further spread to higher latitudes or altitudes is possible in areas with sufficient abundance of definitive hosts, since low winter temperatures are not necessarily an obstacle to the spread of the parasite.
Keywords: stadia vývoje; Limax maximus; hlemýždi; Humans; Angiostrongylus; Snails; larva; infekce hlísticemi řádu Strongylida; krysa rodu Rattus; Angiostrongylus cantonensis; lidé; zvířata; Strongylida Infections; roční období; overwintering; Seasons; Life Cycle Stages; Rats; Larva; Animals; invasive nematode